Use of Mac‐2 binding protein as a biomarker for nonalcoholic fatty liver disease diagnosis. Issue 8 (16th August 2017) - Kamada, Yoshihiro; Ono, Masafumi; Hyogo, Hideyuki; Fujii, Hideki; Sumida, Yoshio; Yamada, Makoto; Mori, Kojiroh; Tanaka, Saiyu; Maekawa, Tomohiro; Ebisutani, Yusuke; Yamamoto, Akiko; Takamatsu, Shinji; et al.
Abstract : In contrast to patients with viral hepatitis, patients with nonalcoholic fatty liver disease (NAFLD) can progress to hepatocellular carcinoma during the initial stages of liver fibrosis. Development and implementation of noninvasive methods for diagnosis and progression prediction are important for effective NAFLD surveillance. Mac‐2 binding protein (Mac‐2bp) is a useful nonalcoholic steatohepatitis (NASH) diagnosis biomarker and a powerful prediction biomarker for NAFLD fibrosis stage. Wisteria floribunda agglutinin (WFA)‐positive Mac‐2bp (WFA + ‐M2BP) is a novel serum fibrosis biomarker for chronic hepatitis C that has clinical validity. Mac‐2bp and WFA + ‐M2BP are also clinical NAFLD biomarker candidates. We examined the efficacy of Mac‐2bp and WFA + ‐M2BP for NAFLD assessment using patients with biopsy‐proven NAFLD (n = 510; NAFLD cohort) and subjects who received a health check‐up (n = 2, 122; check‐up cohort). In the NAFLD cohort, we set the fibrosis predicting cutoff values as 1.80 (F1), 2.21 (F2), and 2.24 μg/mL (F3). In the subjects with fatty liver from the check‐up cohort (n = 1, 291), the serum Mac‐2bp levels were >1.80 μg/mL in 38.6% of the subjects (n = 498), and >2.24 μg/mL in 24.6% of the subjects (n = 318). The NAFLD cohort results indicated that Mac‐2bp and WFA + ‐M2BP were equally useful for NASH diagnosis. During the early stages of fibrosis (F1, F2), the increase in Mac‐2bp was statistically significant but WFA + ‐M2BP did not increase. Logistic regression analysis revealed that Mac‐2bp was an independent determinant for the prediction of advanced fibrosis stage (≥F2), even when adjusted for WFA + ‐M2BP. Immunohistochemical staining of Mac‐2bp revealed that hepatocytes strongly expressed Mac‐2bp in patients with NAFLD. Conclusion : Our results indicated that hepatocyte‐derived Mac‐2bp would be a useful single biomarker for NASH diagnosis and fibrosis stage prediction in patients with NAFLD. ( Hepatology Communications 2017;1:780–791)